Pre-Election Dynamics in Yogyakarta - Rossa, Sherlly; Efendi, Muhammad Sidik; Amilia, Lenny Aurelia; Syahadah, Muhammad Ali; Panuntun, Stefanus Ega Panji (PCD Journal, 2025)
This study examines electoral conflict dynamics in Indonesia's Yogyakarta Special Region, which is identified as the second-most vulnerable region nationally, with a score of 63.67% on the 2024 Election Vulnerability Index (Indeks Kerawanan Pemilu/IKP). A significant driver of this vulnerability is the recurrent conflict among political party-affiliated groups or grassroots organisations (often referred to as "underbows"), which tends to escalate during election periods. This research aims to analyse the historical context and decompose the core factors contributing to these conflicts. It also seeks to formulate a comprehensive, multi-stakeholder roadmap for conflict mitigation ahead of the 2024 general elections. Employing a qualitative, phenomenological approach, the study is theoretically grounded in Paul Wehr's (2019) conflict anatomy framework and the patron–client political-economic perspectives developed by Gerry van Klinken & Ward Berenschot (2018). Our findings reveal five key conflict triggers: historical legacies, personal rivalries, "black campaigns" by political parties, ambiguous security strategies, and entrenched political-economic interests. This research contributes to scientific knowledge by applying and extending conflict anatomy and patron-client theories to the specific context of Indonesian sub-national electoral violence, providing a nuanced understanding of its underlying mechanisms. Based on these insights, we propose practical resolutions, including enhancing civic political education, strengthening law enforcement, and strategically mapping vulnerable areas. These evidence-based recommendations are critical for fostering a more peaceful, participatory, and democratic electoral environment in Yogyakarta.